Triclopyr Absorption and Translocation by Eurasian Watermilfoil (Myriophyllum spicatum) Following Liquid and Granular Applications. Issue 1 (March 2014) - Vassios, Joseph D.; Nissen, Scott J.; Koschnick, Tyler J.; Heilman, Mark A.
Abstract : One method that appears promising for the treatment of Eurasian watermilfoil in areas of high water exchange is the use of herbicide-impregnated granules. Experiments were conducted using liquid triclopyr-triethylamine and granules impregnated with triclopyr-triethylamine to test this theory. Uniform, multistemmed Eurasian watermilfoil plants were selected for these experiments. Plants were treated in clear acrylic cylinders containing 7 L of water with 0.5 mg/L triclopyr as the liquid triethylamine plus 20 kBq 14 C-triclopyr or blank granules impregnated with triclopyr triethylamine plus 20 kBq of 14 C-triclopyr. Plants were harvested 6, 12, 24, 48, 96, and 192 h after treatment (HAT) and the radioactivity in the apical meristems, remaining shoot and root was determined with sample oxidation and liquid scintillation spectroscopy. There were no significant differences in overall herbicide absorption by Eurasian watermilfoil following liquid and granular triclopyr treatments; however, differences were observed between plant parts. Apical meristems accumulated the most radioactivity, whereas roots accumulated very little radioactivity following liquid treatment. Granular applications resulted in 7.5 times more radioactivity in the Eurasian watermilfoil roots then the liquid triclopyr application; therefore, long-term control of well-established Eurasian watermilfoil plants could improve with granular applications, especially in areas where rapid herbicide dilution could be an issue.